Higgs Information and NMSSM at the Large Hadron Collider - Surabhi Gupta; Sudhir Kumar Gupta (Advances in High Energy Physics)
Information theory has proven to be a worthwhile tool for investigating the implications of the Higgs sector in the Next-to-Minimal Supersymmetric Standard Model (NMSSM) using Higgs information at the Large Hadron Collider (LHC) assessed through the entropy constructed by means of the branching ratios of decay channels of the Higgs boson. The present article focuses on the parameter space of supersymmetric extension with an extra term of singlet in light of various experimental constraints. Our findings show the most preferred values of m0, m1/2, A0, tanβ, λ, μeff, neutralino lightest supersymmetric particle (LSP) mχ~10, lighter chargino mχ~1±, singlino mχ~50, and gluino mg~ to be around 1.93 TeV, 1.78 TeV, −3.62 TeV, 27.5, 0.012, 665.7 GeV, 740 GeV, 790 GeV, 11.24 TeV, and 3.70 TeV, respectively, that is compatible with the relic density of dark matter.